Juridical Study on Abuse of Authority in Corruption Crimes: Analysis of Law No. 19 of 2019 concerning the Corruption Eradication Commission - Saragih, Yasmirah Mandasari; Armanda, Wahyu; Novaisal, Ahmad (PT. Riset Press International, 2023)
Eradication of Corruption Crimes is a series of activities to prevent and eradicate the occurrence of criminal acts of corruption through efforts to coordinate, supervise, monitor, investigate, investigate, prosecute, examine before courts, with community participation in accordance with statutory provisions. Corruption is a criminal act which if violated will be sanctioned, traced from the point of view of life and appears as a bad cultural image of the Indonesian nation. Corruption crimes are all negative activities related to embezzlement of funds, bribery and all forms of gratuities that are contrary to law, norms and customs. Traditionally, people can say that Indonesia's identity is corruption. This image is not completely wrong. Because the reality of the complexity of corruption is felt to be not merely a legal issue, but actually a violation of economic and social rights that has an impact on the life of the nation. Talking about corruption will indeed find the fact that corruption involves moral aspects, traits and circumstances that are not good, positions in government agencies or apparatus, misappropriation of power or authority in office due to gifts, economic and political factors, as well as placement of families or groups into officialdom under the authority of the position. In this research, the formulation of the problem is how the juridical review of the crime of abuse of authority in corruption is viewed from Law no. 19 of 2019 and what is the mechanism for filling the positions of the supervisory board of the Corruption Eradication Commission according to Law no. 19 of 2019 also has normative and juridical research methods that are associated with laws and all opinions of legal experts as well as the placement of families or groups into officialdom under the authority of his position. In this research, the formulation of the problem is how the juridical review of the crime of abuse of authority in corruption is viewed from Law no. 19 of 2019 and what is the mechanism for filling the positions of the supervisory board of the Corruption Eradication Commission according to Law no. 19 of 2019 also has normative and juridical research methods that are associated with laws and all opinions of legal experts as well as the placement of families or groups into officialdom under the authority of his position. In this research, the formulation of the problem is how the juridical review of the crime of abuse of authority in corruption is viewed from Law no. 19 of 2019 and what is the mechanism for filling the positions of the supervisory board of the Corruption Eradication Commission according to Law no. 19 of 2019 also has normative and juridical research methods that are associated with laws and all opinions of legal experts.